A philosophy of landscape construction : the vision of built landscapes - Ferguson, Bruce K. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"A Philosophy of Landscape Construction outlines a philosophy of values in landscape construction, demonstrating how integral structures, such as pavements and walls, constitute a key element to how people interact with and inhabit the final design. The book discusses how these structures enable, assist and care for people, negotiating between the dynamic processes of site ecosystems and the soil on which they are founded. They articulate spatial, functional, cultural and ecological meanings. Within this theoretical framework, designers will learn to recognise and insert a set of core values into the most technical design stages to reach their full potential. Offering a new perspective on landscape construction, moving away from the exclusively technical characteristics, this book allows landscape architects to realise the ideal vision for their designs. It is abundantly illustrated with examples from which designers can learn both successes and failures and will be an important companion to any study of built landscapes"--
OCLC-licensed vendor bibliographic record.
Keywords: Landscape design -- Philosophy; Landscape architecture; ARCHITECTURE / Landscape